Study on Seasonal Activity of Predatory Wasps Attacking Honeybee Apis cerana Fab. Colonies in Southern Belt of Kaski District, Nepal - Ranabhat, Nara Bahadur; Tamrakar, Anand Shoba (Journal of Natural History Museum, 2009)
A study was carried out at southern belt of Kaski District during Aug 2003 to July 2004 to study on seasonal activity of predatory wasps viz: Vespa velutina, V. bicolor, V. tropica and V. basalis were observed preying on Apis cerana Fab. in apiaries. Among them Vespa velutina and V. bicolor were the most abundant and common enemies of bees throughout the year. Peak predatory activity occurred to bees ranged from 1.25 to 12.25 per day during different months of the year, when must often coincided with the floral dearth period. Morning and noontime were peak time of attack than late day, which most often coincided with the activity of bees. Key Words: abundant; apiaries; bees; floral dearth; peak time; population Journal of Natural History Museum Vol. 23, 2008 Page 125-128